OPTIMIZATION OF MIXED CONCRETE “SELF COMPACTING” MATERIAL USING FLY ASH, SILICA FUME AND THEIR INFLUENCE OF IRON SLAG STRONG CONTRIBUTION TO THE PRESS - Dwiputro Raharjo; Aman Subakti; Tavio Tavio (Journal of Civil Engineering, 2011)
Self-compacting Concrete (SCC) is an innovation of concrete that does not require the process to occupy formwork vibration (Placing) and compacted (compaction). SCC is able to flow under its own weight, unable to meet or fill formwork (formwork) and reached its highest density. SCC requires a mineral Admixture fly ash and chemical form of Viscocrete a high viscosity in order to meet the specified flowability, whereas other compounds are iron slag waste from steel mill wastes in the form of fine aggregate. Trial mix performed on materials such as fly ash, mineral Admixture fly ash, silica fume, chemical Admixture Sika is viscocrete 10 from Indonesia, and the material is a mixture of iron slag from PT Ispat Indo to determine the optimal composition and meet the requirements of filling ability, passing ability , viscosity and segregation. Tests using the slump cone filling ability, passing ability to use L-box, while the viscosity and segregation using the V-funnel. Compressive strength testing performed with a cylindrical test piece 10 x 20 cm at the age of concrete 3.7, 14, 28 and 56 days. With as many as 495 test specimen for the test object 33 composition of concrete mix design. Each dose was given viscocrete composition from 0.5 to 1.8% by weight of cementitious according to the dose required by Sika Indonesia. While the dose of Silica Fume composition using 0%, 10% and 20% of fly ash pozzolan. The final aim of this study are expected to obtain the optimal material composition of the mixture by generating a maximum compressive strength and price efficient as well.